2022
DOI: 10.3390/nu14102130
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Influence of Food Insecurity and Retail Environments as a Proxy for Structural Racism on the COVID-19 Pandemic in an Urban Setting

Abstract: A collaborative partnership launched the Great Grocer Project (GGP) in March 2021 in Detroit, Michigan where health inequities, including deaths due to COVID-19, have historically been politically determined and informed by socially entrenched norms. Institutional and structural racism has contributed to a lack of diversity in store ownership among Detroit grocers and limited access to high-quality, affordable healthy foods as well as disparate food insecurity among Detroit residents. The GGP seeks to promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Additionally, access to healthier grocery food environments is associated with access to high-quality and healthy foods and beverages and can serve as a potential contributor to healthy food security within communities of color in Metro Detroit [16]. Other research studies have indicated that food stores are health promotion agents and can aid in improving the healthy eating behavior of families [16,70,[74][75][76]. The comparison of the NEMS-SSB scores revealed the negative influence of SSB marketing on children's improving or deteriorating nutritional behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, access to healthier grocery food environments is associated with access to high-quality and healthy foods and beverages and can serve as a potential contributor to healthy food security within communities of color in Metro Detroit [16]. Other research studies have indicated that food stores are health promotion agents and can aid in improving the healthy eating behavior of families [16,70,[74][75][76]. The comparison of the NEMS-SSB scores revealed the negative influence of SSB marketing on children's improving or deteriorating nutritional behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Since genetic changes cannot appear this quickly, environmental factors are the primary determinants for this shift and for shaping nutritionrelated behaviors [12][13][14][15]. This is especially true for low-income ethnic minority families who have limited access to healthy food resources, often because of financial, transportation, and linguistic barriers, and who thus rely on convenience and corner stores within close neighborhoods for purchasing food and beverages [16][17][18][19][20][21][22][23]. Grocery stores within lowincome neighborhoods typically have lower-quality foods with less variety and are the main source of energy-dense nutrition-poor foods and sugar-sweetened beverages [18,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, access to healthier grocery food environments is associated with access to high-quality and healthy foods and beverages and can serve as a potential contributor to healthy food security within communities of color in Metro Detroit [16]. Other research studies have indicated that food stores are health promotion agents and can aid in improving the healthy eating behavior of racial and ethnic minority families [16,60,64,65,66]. The comparison of the NEMS-SSB scores revealed the negative influence of SSB marketing on children's improving or deteriorating nutritional behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Since genetic changes cannot appear this quickly, environmental factors are the primary determinants for this shift and for shaping nutrition-related behaviors [12][13][14][15]. This is especially true for low-income ethnic minority families who have limited access to healthy food resources, often because of financial, transportation, and linguistic barriers, and who thus rely on convenience and corner stores within close neighborhoods for purchasing food and beverages [16][17][18][19][20][21][22][23]. Grocery stores within low-income neighborhoods typically have lower-quality foods with less variety and are the main source of energy-dense nutrition-poor foods and sugar-sweetened beverages [18,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…Participant grocery stores in this study were all large-format, full-service grocery stores with an abundant selection of food offerings. Given that the stores are independently owned vs. corporately owned and located in an urban environment, some food products may sell at higher prices in their stores than competitors (e.g., Wal-Mart) [77][78][79][80]. Participating grocers were located in Hispanic and Latino enclaves in Southwest Detroit and Arab and Chaldean enclaves in North Central Detroit (N = 8 stores), Dearborn (N = 13 stores), Hamtramck (N = 3 stores), and Warren, MI (N = 6 stores).…”
Section: Setting and Characteristicsmentioning
confidence: 99%